2020
DOI: 10.1080/15384047.2020.1727700
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA CCAT1 enhances sensitivity of paclitaxel in prostate cancer via regulating miR-24-3p and FSCN1

Abstract: Drug resistance limits the efficacy of chemotherapy in human cancers. Previous studies reported that long noncoding RNA colon cancer-associated transcript 1 (CCAT1) regulated progression of prostate cancer (PCa). However, the potential role of CCAT1 in the sensitivity of paclitaxel (PTX) in PCa and its mechanism remain largely unknown. The PTX-resistant PCa cells were established in PC3 and DU145 cells by increasing concentrations of PTX. The expressions of CCAT1, microRNA-24-3p (miR-24-3p) and fascin1 (FSCN1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…Subsequently, the presence of miR-24-3p caused a reduction of luciferase activity in both DU145-TXR and PC3-TXR cells. In addition, miR-24-3p over-expression led to even more FSCN1 expression in the cells [17]. Gao et al [18] displayed that miR-24-3p was actually downregulated in CC cells, but the miR-24-3p overexpression suppressed the proliferation of CC cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, the presence of miR-24-3p caused a reduction of luciferase activity in both DU145-TXR and PC3-TXR cells. In addition, miR-24-3p over-expression led to even more FSCN1 expression in the cells [17]. Gao et al [18] displayed that miR-24-3p was actually downregulated in CC cells, but the miR-24-3p overexpression suppressed the proliferation of CC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed that the prospective downstream targets of CCAT1 included miR-24-3p, which may bind to CCAT1 in RNA pull-down, RIP as well as luciferase assays [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations